Nonpharmacological interventions to reduce sedation/general anaesthesia in paediatric patients undergoing magnetic resonance imaging: A systematic review and meta‐analysis protocol. Issue 9 (27th May 2021) - Hybschmann, Jane; Povlsen, Nanna E.; Sørensen, Jette L.; Afshari, Arash; Borgwardt, Lise; Berntsen, Marianne; Madsen, Thurid W.; Gjærde, Line K.
Abstract: Background: Magnetic resonance imaging is frequently used in paediatrics and requires the child/adolescent to remain still for 45 min or more. The long and narrow scanner gantry makes loud noises and may cause anxiety. To complete the procedure, children and adolescents are often sedated or receive general anaesthesia. Our primary aim is to determine whether nonpharmacological interventions designed to mentally prepare, support or distract children, and adolescents are effective in reducing the need for sedation and general anaesthesia. Methods: We will conduct a systematic review with meta‐analysis by searching the following electronic databases: Ovid MEDLINE, CINAHL, Embase and CENTRAL, as well as databases for ongoing trials. Eligibility criteria are based on the participants, intervention, comparator and outcome (PICO) framework. We will include intervention studies with comparator group(s) with no restriction on date. Two reviewers will independently screen titles/abstracts, and three reviewers will assess the full texts of potentially relevant studies. Data will be extracted, and the methodological quality will be assessed using Cochrane risk of bias tools. If the data allow, we will perform a meta‐analysis using a random effects model on the primary outcome, sedation/general anaesthesia. A narrative synthesis will supplement the statistical analysis. Quality of evidence for the primary outcome will be assessed using the grading of recommendations, assessment, development and evaluations (GRADE) approach. Discussion: Our findings will provide directions for future research and may guide clinicians in terms of which type(s) of intervention(s) to implement to reduce the use of sedation/general anaesthesia during paediatric magnetic resonance imaging.